Material Supply Model with the Perspective of Capacity Planning and Material Limitations to Minimize the Risk of Production Uncertainty in SMEs Tanggulangin Sidoarjo - Rony Prabowo; Wanvia Vangesti (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2026)
SMEs are a very important pillar of the Indonesian economy, because apart from being able to produce various types of community needs and being a contributor to regional income, they are also able to absorb non-formal workers with low education. In Sidoarjo Regency, East Java, there is an SME cluster area in Tanggulangin village with a total of 328 SMEs with 18,464 workers. This UKM produces various types of handmade crafts which are in great demand by local, non-provincial and overseas consumers. This research is very important for SMEs in Tanggulangin because with the existence of a material supply model that takes into account the perspective of capacity planning and material limitations, it will really help SMEs to purchase materials effectively and efficiently in order to meet consumer demand according to the number of orders so that the profits obtained by SMEs are optimal. The MRP method is used for material requirements planning, RCCP for rough-cut capacity validation, CCR for bottleneck identification, TOC for bottleneck optimization, and Monte Carlo for risk analysis. The integration of Monte Carlo, RCCP, TOC, CCR, and MRP results in a capacity planning system that is structured (spanning from planning to risk evaluation), constraint-based (avoiding over-optimism), and adaptive to uncertainty. Monte Carlo simulation models the operation of two machines handled by a single operator with an optimal operating time of 5 hours; RCCP indicates an optimal production process of one batch with a 45 kg capacity; and the ideal TOC value falls within a range where process transitions must occur between a minimum of 3 minutes and a maximum of 45 minutes. In the work element of cutting rolls of tanned leather into patterned leather pieces one by one at the leather craft product work center 1, the capacity requirements cannot be met using only 2 work shifts. To anticipate capacity shortages that will occur throughout 2024, this can be done by adding overtime hours, extra days, MRP revisions, and MRP revisions with overtime. If proposed strategy 1 (additional overtime hours) is implemented, it would cost IDR 153,266,618 in one year. And if proposed strategy 2 (extra day) is implemented, it will cost IDR 219,513,728 in one year. The third proposed strategy, namely MRP revision, requires no costs at all to implement. The costs incurred if strategy 4 (MRP revision with over time) is implemented is IDR 145,687,500 in one year.